Colloidal Processing of Zirconium Diboride Ultra‐High Temperature Ceramics. Issue 8 (21st May 2013) - Tallon, Carolina; Chavara, Dorji; Gillen, Andrew; Riley, Daniel; Edwards, Lyndon; Moricca, Sam; Franks, George V.; Wei, W.‐C.
<x xml:space="preserve">Abstract</x> Colloidal processing of the Ultra‐High Temperature Ceramic (UHTC) zirconium diboride (ZrB2) to develop near−net‐shaping techniques has been investigated. The use of the colloidal processing technique produces higher particle packing that ultimately enables achieving greater densification at lower temperatures and pressures, even pressureless sintering. ZrB2 suspension formulations have been optimized in terms of rheological behavior. Suspensions were shaped into green bodies (63% relative density) using slip casting. The densification was carried out at 1900°C, 2000°C, and 2100°C, using both hot pressing at 40 MPa and pressureless sintering. The colloidally processed materials were compared with materials prepared by a conventional dry processing route (cold pressed at 50 MPa) and subjected to the same densification procedures. Sintered densities for samples produced by the colloidal route are higher than produced by the dry route (up to 99.5% relative density by hot pressing), even when pressureless sintering is performed (more than 90% relative density). The promising results are considered as a starting point for the fabrication of complex‐shaped components that can be densified at lower sintering temperatures without pressure.